Atomic Scale Origin of Metal Ion Release from Hip Implant Taper Junctions. Issue 5 (21st January 2020) - Balachandran, Shanoob; Zachariah, Zita; Fischer, Alfons; Mayweg, David; Wimmer, Markus A.; Raabe, Dierk; Herbig, Michael
Abstract: Millions worldwide suffer from arthritis of the hips, and total hip replacement is a clinically successful treatment for end‐stage arthritis patients. Typical hip implants incorporate a cobalt alloy (Co–Cr–Mo) femoral head fixed on a titanium alloy (Ti‐6Al‐4V) femoral stem via a Morse taper junction. However, fretting and corrosion at this junction can cause release of wear particles and metal ions from the metallic implant, leading to local and systemic toxicity in patients. This study is a multiscale structural‐chemical investigation, ranging from the micrometer down to the atomic scale, of the underlying mechanisms leading to metal ion release from such taper junctions. Correlative transmission electron microscopy and atom probe tomography reveals microstructural and compositional alterations in the subsurface of the titanium alloy subjected to in vitro gross‐slip fretting against the cobalt alloy. Even though the cobalt alloy is comparatively more wear‐resistant, changes in the titanium alloy promote tribocorrosion and subsequent degradation of the cobalt alloy. These observations regarding the concurrent occurrence of electrochemical and tribological phenomena are vital to further improve the design and performance of taper junctions in similar environments. Abstract : Corrosion and wear at taper junctions in metallic implants can release toxic metal ions into the body. Although biomedical cobalt alloys have a higher hardness than titanium alloys, this study finds that changes on the titanium alloy during fretting can promote tribocorrosion in the cobalt alloy. Such insights can be used to improve material design in taper junctions and implants.